Note on the Professionality of Mathematics and Science Teachers in The Post-Covid-19 Pandemic - Gregoria Ariyanti; Mateus Yumarnamto; Kristin Anggraini; Maria Josephine Kriesye (Jurnal Paedagogy, 2023)
This study aims to analyze mathematics and science teachers' professional identity and competence during the Covid-19 pandemic. This study used the literature review method with data analysis using the content analysis method. This study used documentation instruments published in nationally accredited journals, indexed proceedings, Scopus-indexed international journals, and teacher's competence books. The results were some of the skills that mathematics and science teachers need this time. Several skills were the experience of implementing learning during the Covid-19 pandemic, including scientific literacy skills, classroom management skills both online and offline, including actively involving students, and communication skills, especially with parents.